Increased Corrosion Resistance of Zinc Magnesium Aluminum Galvanised Coating through Germanium Additions. (5th January 2017) - Mehraban, Shahin; Malone, Jack; Lavery, Nicholas; Sullivan, James; Penney, David; Brown, Steve
Abstract : The corrosion performance of a Zinc Magnesium Aluminium alloy was shown to improve through the addition of a quaternary element, Germanium. Improved corrosion resistance can be attributed to microstructural changes in the alloy due to Ge addition while in the molten state. The proportion of the most active MgZn2 phase which has been shown to initiate the corrosion reaction in a ZMA alloy was reduced thorough the formation of Mg2Ge crystals. The formation of crystal structures within the alloy also increased the heterogeneous nucleation of the primary zinc phase. The Scanning Vibrating Electrode Technique (SVET) was used to measure the rate of corrosion, anode life and zinc loss of the alloy samples. The results showed a zinc loss of around 50% when compared to standard ZMA alloy without Ge addition.